2017
DOI: 10.2105/ajph.2017.303766
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Walking in the Hartsfield-Jackson Atlanta International Airport: The Walk to Fly Study

Abstract: The Walk to Fly study demonstrated a significant and sustained increase in the number of airport travelers choosing to walk. Providing signage about options to walk in busy locations where reasonable walking options are available may improve population levels of physical activity and therefore improve public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…However, in the studies that reported data on the general population, children and persons with children, disabled persons, persons with luggage and, in online studies, persons under the age of 18 were excluded. Most studies were conducted in the UK [77, 81, 8489, 92, 95, 105], followed by online studies mostly without geographical focus [101104, 106108], and studies from the USA [76, 78, 79, 97, 98, 109], and Hong Kong [75, 80]. There was one study each from Singapore [96], Japan [91], Denmark [83], Sweden [82], Germany [90], Belgium [100], France [99], South Africa [93], and Spain [94].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the studies that reported data on the general population, children and persons with children, disabled persons, persons with luggage and, in online studies, persons under the age of 18 were excluded. Most studies were conducted in the UK [77, 81, 8489, 92, 95, 105], followed by online studies mostly without geographical focus [101104, 106108], and studies from the USA [76, 78, 79, 97, 98, 109], and Hong Kong [75, 80]. There was one study each from Singapore [96], Japan [91], Denmark [83], Sweden [82], Germany [90], Belgium [100], France [99], South Africa [93], and Spain [94].…”
Section: Resultsmentioning
confidence: 99%
“…There was one study each from Singapore [96], Japan [91], Denmark [83], Sweden [82], Germany [90], Belgium [100], France [99], South Africa [93], and Spain [94]. Most studies were conducted in train stations/underground train stations [78, 79, 8183, 8992, 94, 96, 99, 100], followed by studies in malls/shopping malls [7678, 8488, 95, 100], airports [79, 97, 98, 109], pedestrian transit systems [80, 82], two public buildings [79, 93], and one bus station [78]. Eight studies were conducted online only [101108].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when individuals gain access to healthy foods, food-purchasing patterns may not change [9]. A burgeoning line of research has focused on ways to encourage healthier behaviors at the point of decision, both in food choice and physical activity [1012]. Point-of-decision prompts (PDPs) aim to disrupt habitual, unhealthy choices—by informing or persuading people—at the moment they are making a choice.…”
Section: Introductionmentioning
confidence: 99%
“… 3. Most of the studies of soft regulation at airports involve micro-issues including the encouragement of walking (Bellettiere et al, 2017; Fulton et al, 2017), the more efficient use of men’s urinals (Thaler, 2016), and the disincentivizing of smoking (Schmidt et al, 2016). …”
mentioning
confidence: 99%